Mantle metasomatism at the edge of a retreating subduction zone: late neogene lamprophyres from the island of Kos, Greece - Soder, Christian; Altherr, Rainer; Romer, Rolf L. (Journal of petrology, 2016)
The island of Kos at the eastern end of the South Aegean Volcanic Arc hosts numerous late Neogene amphibole- and mica-bearing lamprophyres.
Gesehen am 08.05.2020